WAITING TIME RELATED TO OUTPATIENT SATISFACTION AT GUNUNG MARIA HOSPITAL TOMOHON - Frankly Oktavian Palendeng; Sri Rejeki Monica Suparlan; Ake Royke Calvin Langingi (PT. Jurnal Center Indonesia Publisher, 2025)
One measure of service success is patient satisfaction; in the world of health, patient satisfaction indicates that the services provided have been delivered properly by health workers. The purpose of this study was to analyze the relationship between waiting time and outpatient satisfaction at Gunung Maria Tomohon Hospital. The method used in this research is quantitative research which is descriptive analytic using a cross-sectional study approach with a sample of 266 respondents (total sampling) with univariate and bivariate analysis. The results showed that based on the results of the chi-square test, a value of p = 0.001 (<α = 0.05) was obtained, indicating that there is a relationship between waiting time and outpatient satisfaction at Gunung Maria Tomohon Hospital. Based on the results of the analysis, it can be concluded that there is a relationship between waiting time and outpatient satisfaction at the Outpatient Polyclinic of Mount Maria Tomohon Hospital. As a suggestion for hospital leaders, especially for outpatient directors at Gunung Maria Tomohon Hospital, it is recommended to set health service standards, particularly for outpatients, to enhance their satisfaction.